An Analysis of Validity and Reliability of a Teacher-made Test on Descriptive Text: Case Study to Tenth Grade Office Administration Students at SMKN 3 Pontianak - Nurwinda Laili Puspitasari; Nur Ulyasari; Yohanes Gatot Sutapa Yuliana; Clarry Sada (Jurnal Sinestesia, 2023)
This study aimed to analyse the connection between the test items' difficulty and discrimination indices in order to investigate the validity and reliability of a teacher-made test on descriptive text in SMKN 3 Pontianak. The purpose of this analysis was to ascertain if the test items accurately assessed the students' critical thinking abilities. This study used case research design. The test used in this study was created by an English teacher for office administration students in the tenth grade. The test consisted of 20 multiple-choice questions with a descriptive text. Documentation served as the research tool in this study. The researchers aimed to evaluate the degree to which the test items effectively assessed the students' abilities and comprehension of the descriptive text by looking at the test items' levels of difficulty and discrimination. The analysis's findings can shed light on the reliability of the test items as well as how well they assess students' language and critical thinking abilities. The results of the study also support the continuous efforts to increase the reliability of assessments created by teachers and to better evaluate students' learning outcomes in the context of EFL training.